Concept of Supervision of Learning Process in Increasing the Quality of Education Results in Madrasah - Wahyu Wahyu (International Journal of Nusantara Islam, 2020)
This research focuses on the supervision of learning which is a coaching activity planned to assist teachers and school staff in doing work effectively in order to improve the learning process. Educational supervision activities are needed by teachers, because for teachers who work every day at school, no other party is closer and knows of all their activities, except the School Principal. The method used in this research is descriptive method with a qualitative approach. The conclusion in this study is the teacher is one of the determinants of the low quality of educational outcomes. Because there is a direct relationship between teacher performance with student achievement. The low quality of education in Indonesia is the main cause of the low quality of Indonesian human resources. Therefore, educational supervision is needed to improve the quality of education.